The Influence of Leadership Style and Work Motivation on Employee Performance in the Oil Palm Processing Industry: A Study on PT Sawitmas Nugraha Perdana Sampit - M. Thamrin Noor; Hari Susanto; Rinni Wardani; Ahmad Rudini; Deky Prasetyo; Norhidayah (Lembaga Publikasi Ilmiah Nusantara, 2026)
Employee performance is a critical determinant of organizational competitiveness and sustainability, particularly in labor-intensive industries such as palm oil processing. Although previous studies have confirmed the importance of leadership style and work motivation in influencing employee performance, empirical findings remain inconsistent across organizational settings, indicating the need for further investigation in specific industrial contexts. Limited studies have also simultaneously examined the relative contribution of leadership style and work motivation in the Indonesian palm oil processing sector. This study aims to analyze the influence of leadership style and work motivation on employee performance at PT Sawitmas Nugraha Perdana Sampit. Using a quantitative approach with a cross-sectional design, data were collected from 38 employees through a saturated sampling technique and analyzed using multiple linear regression. The results reveal that leadership style has a positive and significant effect on employee performance (β = 0.141; t = 2.358; p = 0.024), while work motivation exerts a stronger positive effect (β = 0.764; t = 8.698; p < 0.001). Simultaneously, both variables significantly influence employee performance (F = 68.367; p < 0.001) and explain 79.6% of performance variation (R² = 0.796). The novelty of this study lies in providing empirical evidence from the palm oil processing industry, demonstrating that work motivation contributes more substantially to employee performance than leadership style. These findings enrich human resource management literature and offer practical implications for managers in designing leadership development and employee motivation strategies to improve organizational productivity.